The North Sumatra MUI’s Fatwas on Zakat: Analysis of Fatwa Methods and the Influence of School Thought - Firmansyah, Heri; Pagar, Pagar; Amar Adly, Muhammad (Institut Agama Islam Negeri Curup, 2022)
This paper examines the methodology of the North Sumatran MUI fatwas, especially those are relating to the influence of schools on the North Sumatran MUI fatwas related to the issue of zakat from 2000-2010. There are 3 samples of fatwas used in this study, namely: first, the fatwa on the law of issuing zakat fitrah with money (qimah) and the amount, second, on the law of paying zakat not to amil and third, the fatwa about zakat on agriculture and plantations. The method used is content analysis. In the study, it was found that from a methodological, the North Sumatra MUI in finding the fatwa law used three theories, namely bayani, ta'lili and istislahi. On the issue of the influence of schools of thought, in the fatwa of the North Sumatran MUI, it was found that the fatwa of the North Sumatran MUI was influenced by various schools of thought and not dominated by a particular school. In this study influenced by the Hanafi, Shafi'i and Hanbali schools. Although the North Sumatran MUI considers the importance of school thought to be taken into consideration, it does not mean that the North Sumatran MUI does not dare to leave the school of thought and issue new laws that come out of the school of thought by using various methods which in this study use the talfiq method.